Two new Ceratobasidium species causing white thread blight on tropical plants in Brazil - de Melo, Maruzanete P.; Matos, Kedma S.; Moreira, Silvino I.; Silva, Fabiano F.; Conceição, Grace H. [UNESP]; Nechet, Kátia L.; Halfeld-Vieira, Bernardo A.; Beserra Júnior, José E. A.; Ventura, José A.; Costa, Hélcio; Furtado, Edson L. [UNESP]; Alves, Eduardo; et al. (Springer Nature, 2018)
White thread blight is one of the most common diseases affecting several tree species that grow in warm and humid regions. The typical symptoms of this disease include blighted leaves hanging by a white thread of fungal hyphae. Leaf samples exhibiting white thread blight symptoms were collected from neem (Azadirachta indica A. Juss) and Brazilian cherry pitanga (Eugenia uniflora L.) plants in Northeastern Brazil, and from Indian green-tea (Camellia sinensis (L.) O. Kuntze), coffee (Coffea arabica L.), and persimmon (Diospyros kaki L.) in agricultural areas neighboring the Atlantic forest in Southeastern Brazil. Fungal isolates were obtained indirectly from leaf fragments or directly by transferring mycelia and sclerotia to culture medium. Bright field and scanning electron microscopy images revealed the association of Rhizoctonia-like hyphae and basidiospores with the infected leaves. In pathogenicity tests, Rhizoctonia-like fungal isolates induced leaf necrosis on their hosts, and the pathogens were re-isolated from inoculated plants. Phylogenetic analyses based on sequences of the ITS rRNA region indicated the occurrence of Ceratobasidium lineages distinct from previously reported Ceratobasidium species. Our study leads to the description of two new species of Ceratobasidium: the fungal isolates from A. indica, C. sinensis, and E. uniflora were classified as Ceratobasidium niltonsouzanum sp. nov., and those obtained from C. arabica and D. kaki as Ceratobasidium chavesanum sp. nov.
Keywords: Binucleate Rhizoctonia; Phylogenetic analysis